Penerapan Model Course Review Horay Pada Pembelajaran IPS di Kelas IV SDN Ciputat 04 Kota Tangerang Selatan - Ajat Sudrajat; Fitra Jaya (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2022)
The purpose of this study was to determine the improvement of social studies learning outcomes for class IV at SDN Ciputat 04, South Tangerang City through the implementation of the course review horay learning model. This study uses the Class Action Research (CAR) method according to Kemmis and Tanggart which consists of four stages of activity in each cycle, namely: (1) planning, (2) action, (3) observation, and (4) reflection. The results showed an increase of 89% of the number of fourth grade students in the second cycle. This shows that there is an increase that exceeds the target set by the previous researchers, which is 80%. Thus it can be concluded that classroom action research on social studies subjects for class IV SDN Ciputat 04 South Tangerang City using the Course Review Horay model has succeeded in improving student learning outcomes. In addition, the implementation of the Course Review Horay model can also create meaningful learning for students.Keywords: learning model; course review horay; social studies learning; learning outcomes